CHANGES IN THE PARAMETERS OF THE IMMUNE SYSTEM UNDER THE INFLUENCE OF IMMUNOCORRECTIVE THERAPY IN WOMEN WITH CERVICAL INTRAEPITHELIAL NEOPLASIA - Kalandarova, A.N.; Aripova, T.U. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
a comparative analysis of the parameters of cellular immunity in women with infectious-inflammatory diseases of the cervix uteri associated with cervical intraepithelial neoplasia. Material and methods: under supervision were 64 women with CIN I and II degrees aged 25 to 49 years (mean age 36.8 ± 6.7 years). The diagnosis was made on the basis of the clinical picture and the results of laboratory and instrumental studies. 31 women of the 1st group received basic treatment, 33 patients of the 2nd group received the bioflazid per os preparation starting from 15-20 drops to 30 drops per day in three doses against the background of basic therapy. Results: Immediately after the completion of therapy, clinical manifestations of vulvovaginitis and cervicitis were noted, cessation of abnormal vaginal discharge, lack of discomfort during sexual intercourse and urination in 90.6% of the 1st patients and in 96.4% of the 2nd group, which was statistically significant compared with baseline (p <0.05). Normal values of the vaginal pH after the completion of therapy were recorded in 26 (81.3%) patients who received combined treatment with bioflazid per os and locally. Conclusions: The data obtained confirm the effectiveness of the use of bioflazid in complex treatment, in which there is a positive trend not only in clinical indicators, but also in parameters of the immune system.